2001
DOI: 10.1034/j.1600-0579.2001.005001023.x
|View full text |Cite
|
Sign up to set email alerts
|

Report on the development of a new dental curriculum at Helsinki

Abstract: A review of the dental curriculum was undertaken in Helsinki in the mid 90s. The objectives of the new curriculum were to reinforce the links between basic biomedical and dental sciences in order to give more emphasis to oral medicine and comprehensive dental care. Furthermore, the curriculum needed to promote an interdisciplinary approach and encourage students to understand dental diseases in relation to the community at large. A two-year, topic-based, preclinical curriculum, fully integrated with medical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…Previous studies have also shown a tendency for the majority of the students to prefer to continue their education towards a specialty degree [7,13-15]. This has implications for the dental workforce planning in any country.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have also shown a tendency for the majority of the students to prefer to continue their education towards a specialty degree [7,13-15]. This has implications for the dental workforce planning in any country.…”
Section: Introductionmentioning
confidence: 93%
“…In a study in Nigeria, interest, prestige, good job opportunities abroad as well as regular work hours were the top ranked motives for studying dentistry [5]. The need for the dental education system to train students who have a sense of social responsibility in view of these findings had been emphasized earlier [3,6,7]. Sex differences have also been reported in students’ study motives and career preferences [5,7-12].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, similar thematic approaches have been reported in the past, in particular as complementary pathways to the content approaches used in the first 2 years of the medical school curriculum at the same institution [24][25][26]. Utilizing these thematic streams, course material would be centered around concepts rather than specific small focused courses.…”
Section: Dental Curriculum Issues and Solutions In The United States mentioning
confidence: 82%
“…La educación dental está estrechamente ligada la investigación en ciencias de la salud (9) . Por esta razón, las escuelas de odontología representan centros de excelencia para las comunidades donde están insertas (10) , proveyendo de valiosa información acerca del estado epidemiológico de una comunidad así como la efectividad de las intervenciones que en ella se realizan.…”
Section: Discussionunclassified